An Evaluation of an Assignment Management and Monitoring Tool to Support Student Assessment - Mee Chin Wee; Zaitun Abu Bakar (UiTM Publisher, 2006)
Information and communication technology (ICT) has influenced many fields and revolutionized the way they function. One of the major fields is education. In institutions of higher education, lecturers rely on ICT tools such as the Internet, email, word processing and presentation software for assistance in teaching and learning. Automated assignment management is another important technique that is used in managing student assessments. However, existing systems have limited features to support assignment supervision. The aim of this paper is to present a prototype called Lightweight Assignment Management Prototype (LAMP) and its evaluation. This prototype is designed to assist in the assignment monitoring process, which is not supported by existing systems. The paper starts with a description of the assignment supervision process at the higher education level. Then the tools available in supporting assignment management are reviewed. This is followed by a proposed scenario for assignment management and monitoring. The methodology used to test the prototype is then presented. A few user interfaces of the prototype's main modules, from both the lecturers' and the students' perspectives, are described. Finally, the results of the evaluation are discussed.